Determination of Stoichiometry and Stability Constant of Cd(II) and Zn(II) Complexes with Pyrazole Based Ligands in Mixed Solvent (EtOH-H2O) - Elsherif, Khaled Muftah; Zubi, Ahmed; Najar, Adel; Bin Ghashir, Hamida (Journal of Pure & Applied Sciences, 2022)
A Spectrophotometric investigation was applied on the complexation of 1,3-bis (3-(2-pyridyl) pyrazol-1-ylmethyl) benzene (1,3-PPB) and 1,4-bis (3-(2-pyridyl) pyrazol-1-ylmethyl) benzene (1,4-PPB) with Zn(II) and Cd(II) ions in a mixed (1:1) solvent of water and ethanol. The mole ratio methodology was used to calculate the stoichiometry, molar absorptivity, and stability constant values. Some experimental conditions have been investigated, including pH, ionic strength, solvent composition, and time. The results revealed the production of 1:1 complexes. In terms of ligands, 1,4-PPB was more stable than 1,3-PPB, whereas Cd(II) complexes were more stable than Zn(II) complexes. The complexes' molar absorptivity values were determined to be 5744, 10019, 9414, and 17716 l.mol-1.cm-1 for Cd-1,3-PPB, Cd-1,4-PPB, Zn-1,3-PBB, and Zn-1,4-PBB, respectively. The sensitivities for Cd and Zn estimation by complexation with 1,3-PPB and 1,4-PPB, respectively, were determined to be 0.051, 0.089, 0.114, and 0.271 mg.l-1.